Kebijakan dan Implementasi Strategi Anti-Fraud: Studi pada PT. Bank UOB Indonesia - Fransiska Tarasita Asmara; Akhmad Riduwan; Maswar Patuh Priyadi (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
Based on the many fraud cases experienced by PT Bank UOB Indonesia, the implementation of the anti-fraud strategy at PT Bank UOB Indonesia refers to the implementation of policies issued by PT Bank UOB Indonesia in order to minimize fraud cases. This study aims to determine the policies and implementation of anti-fraud strategies at PT Bank UOB Indonesia. The object of this research is the Integrated Fraud Management Division. This research was conducted using a case study qualitative research method and using data analysis techniques Miles and Huberman. The data collection techniques in this study were participant observation, in-depth interviews and documentation. Selection of sources is carried out by purposive sampling method, in which sources are selected with specific considerations and goals. The results show that the policy and implementation of the Anti-Fraud strategy have been implemented in accordance with Bank Indonesia Circular No.13/28/DPNP dated 9 December 2011 concerning the Implementation of Anti-Fraud Strategies for Commercial Banks, however there are still deficiencies caused by obstacles in its implementation. namely the lack of awareness of employees to report all indications of fraud, very minimal employee rotation, frequent information about surprise audits that cannot be kept secret, and the recruitment pattern adopted by PT Bank UOB Indonesia does not include material on fraud awareness.